SERUM MAGNESIUM AS A PROGNOSTIC INDICATOR IN ACUTE CORONARY SYNDROMES AND COMPARISON WITH CORONARY PROGNOSTIC INDEX - AKHILESH, ANNADATHA ACHYUTA; VARMA, ANUJ; KUMAR, SUNIL (International Journal of Psychosocial Rehabilitation, 2020)
Coronary heart disease is one of the leading causes of morbidity and mortality in the world. Various risk factors at different levels have been extensively studied in this disease and various relationships of factors with the disease have been already been established. It is not far ahead by the time we start correlating new factors with CHD. Electrolyte studies in Acute Coronary Syndromes have been studied but there has been no ground breaking research which would change the approach towards managing a case of ACS and CHD (1-4). Serum Magnesium is second most major cation in the body with variety of functions in the body. Majority of the Serum Magnesium in the body is through the dietary sources and majority of the adults do not consume the average daily requirement of the same. Magnesium has been reported to cause arrhythmias and has a role in cardiac metabolism (5-10).